EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT DENGAN PETA KONSEP PADA POKOK BAHASAN TRIGONOMETRI DITINJAU DARI EMOTIONAL SPIRITUAL QUOTIENT DAN KONSEP DIRI SISWA SMA/MA KELAS XI IPA SE-KABUPATEN BANYUMAS - Rahayu, Nastiti; Usodo, Budi; Mardiyana, Mardiyana (Journal of Mathematics and Mathematics Education, 2014)
Abstract: This research was conducted to find out: (1) which produces better mathematics achievement: students who were given TGT cooperative learning with mind mapping, TGT cooperative learning, or conventional learning; students who have high emotional spiritual intelligence or low one; students who have a positive or negative self-concept. and (2) which is better, the mathematics achievement of students in each category of spiritual emotional intelligence (high or low) and the category of self-concept (positive or negative) on the TGT with mind mapping, TGT cooperative learning, and conventional learning. This study used a quasi-experimental study with a factorial design 3x2x2. The population in this study were all students of Science Second Grade Students of senior high schools in Banyumas Regency in the Academic Year of 2012/2013. The hypothesis test used three-way analysis of variance with unbalanced cell. Based on the analysis, we concluded as follows. (1) The mathematics achievement of students given TGT learning model with mind mapping was better than students given TGT learning model and the conventional model of learning. However, there was no difference in achievement between students given TGT learning models with conventional learning model; there was no difference in mathematics achievement of students with high emotional spiritual intelligence with students with low emotional spiritual intelligence; the mathematics achievement of students with positive self-concepts better than students with a negative self-concept. (2) In every model of learning, students with high emotional spiritual intelligence always provide a better learning achievement than students with low emotional spiritual intelligence. In the learning model TGT with mind mapping, students with a positive self-concept provided better mathematics achievement than students with a negative self-concept, while in the TGT and conventional learning model, there was no difference in achievement between students with a positive self-concept and students with negative self-concept.Key words: Mathematics Learning Achievement, TGT, Mind Mapping, ESQ, Self Concept